Verification Method of Complex Web-Services - Elena, Tkachova; Saad, Issam; Yahya, Abdulghafoor Raed (Journal of Future Internet, 2014)
In the article proposed formalisms for defining rules of Web-services orchestration and choreography that allows to combine elements of a distributed system in a single system. Proposed approach allows to perform formal association of individual system components into a single unit. Proposed verification method for distributed systems based on the model approach. E-networks are models for verification of distributed systems. Web-service’s safety check is performed by finding deadlock conditions or any deviation from the specification process. This method allows taking into account the asynchronous nature of complex services and also performing stateful inspection: check for different Web-service consistency, check orchestration and choreography compatibility requirements for each service.